Revisiting Bioprospecting in the Southern Ocean in the Context of the BBNJ Negotiations - Nickels, Philipp Peter (Ocean Development & International Law, 2020)
This article revisits marine bioprospecting in the Southern Ocean in the context of the efforts to develop an international legally binding instrument (ILBI) under the United Nations Convention on the Law of the Sea on the conservation and sustainable use of marine biological diversity in areas beyond national jurisdiction. After briefly introducing the Antarctic Treaty System (ATS), this article examines the extent to which the ILBI will likely spatially overlap with the ATS. As the next step, it is highlighted that future provisions on marine genetic resources (MGRs) in the ILBI might substantively differ from the way the ATS currently regulates bioprospecting. Based on that, the final section reflects on how the ILBI will normatively and institutionally relate to the ATS.